Remarks at the G20 Finance Ministers and Central Bank Governors Meeting - Malpass, David (World Bank, Washington, DC, 2020)
World Bank Group President David Malpass spoke about the recession in advanced economies that is less severe than had been feared, but in most developing economies, it has become a depression, especially for the poorest. The World Bank Group was able to launch health emergency programs in one hundred and eleven countries and begin a surge in their grants and highly concessional lending that will reach the limits of our capital structure and commitment authority. The goals for debt relief in the Spring meetings were fiscal savings for the poorest countries, greater debt transparency, and a path forward for countries in debt distress. He insisted that it’s important to note that the Debt Service Suspension Initiative (DSSI) defers payments into the future but doesn’t reduce them. The World Bank Group Board approved a package of up to twelve billion US dollars to expand the fast-track Coronavirus (COVID-19) response for the purchase and distribution of Coronavirus (COVID-19) vaccines, tests and treatments. He will propose to IDA Deputies later this month creating a twenty-five billion US dollars supplemental COVID Emergency Financing Package. He concluded that even in the midst of a once-in-a-century crisis, he has confidence that sustainable solutions will emerge, in part by embracing constructive change.